2020
DOI: 10.1167/tvst.9.10.28
|View full text |Cite
|
Sign up to set email alerts
|

Macular Function in Early and Intermediate Age-related Macular Degeneration: Correlation with the Simplified Thea Risk Assessment Scale (STARS)

Abstract: Macular function in early and intermediate age-related macular degeneration: Correlation with the simplified thea risk assessment scale (STARS). Trans

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The results showed that microanatomic abnormalities of the macula were correlated with abnormalities in functional parameters (acuity, fERG), indicating early losses in retinal function. 13 , 21 In addition, the extent of RORA, a parameter correlated with visual acuity and fERG amplitude, significantly predicted the progression of disease at 12 months. Our findings support the diagnostic power and predictivity of morphofunctional assessments in ne-AMD eyes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The results showed that microanatomic abnormalities of the macula were correlated with abnormalities in functional parameters (acuity, fERG), indicating early losses in retinal function. 13 , 21 In addition, the extent of RORA, a parameter correlated with visual acuity and fERG amplitude, significantly predicted the progression of disease at 12 months. Our findings support the diagnostic power and predictivity of morphofunctional assessments in ne-AMD eyes.…”
Section: Discussionmentioning
confidence: 96%
“…11 , 14 In other studies, the combination of microperimetric sensitivity and low luminance deficit assessment have been reported as suboptimal in predicting the progression of disease. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Correlations between the amplitude of FERG and ageing (Messenio et al 2013) as well as intermediate AMD have been reported (Falsini et al 1999(Falsini et al , 2000(Falsini et al , 2007; two recent works have correlated decline in FERG amplitude with subjective deterioration of vision quality (Minnella et al 2020) and to development of incomplete RPE and outer retinal atrophy (iRORA, Wu et al, 2021) in early and intermediate AMD patients (Savastano et al 2020). Interestingly, mean FERG amplitude of iAMD patients in Savastano et al was extremely close to that measured in our patients (mean amplitude: 1.1 µV versus 1.15 µV, respectively), possibly attesting for the reproducibility of FERG recording results.…”
Section: Discussionmentioning
confidence: 97%
“…Few studies have instead explored the performance of focal electroretinogram (FERG) in early and intermediate AMD (Seiple et al 1986;Falsini et al 2000Falsini et al , 2007Minnella et al 2020;Savastano et al 2020), and none has compared it to macular function testing through microperimetry.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire showed good discrimination, allowing stratification of subjects according to the risk of AMD (low, moderate, high). The translational relevance of the STARS ® score in predicting macular function in early and intermediate AMD has been recently pointed out: STARS ® is able to predict central retinal function with a high degree of accuracy, as assessed by full-field electroretinogram, which suggests that both parameters can be combined to assess the clinical risk for loss of visual function even in the early disease stages [37].…”
Section: Introductionmentioning
confidence: 99%